KELIMPAHAN, KOMPOSISI, DAN SEBARAN IKTIOPLANKTON DI LAUTARAFURA [Abundance, composition, and distribution of ichthyoplankton in Arafura Sea] - Karsono Wagiyo (Jurnal Iktiologi Indonesia, 2007)
Study was conducted in Arafura Sea in 2006. The area was divided to four sub-areas; namely West of Aru Island, East of Aru Island, West of Mapi and Mimika, and Tanjung Dolak. In the west of Aru Island we found 26 families of ichthyoplankton, in which the dominant were Clupeidae, Labridae, and Teraponidae. Larvae abundance was mean 204 individuals/1000 m3, ranged from 16 ind./ 1000 m3 to 1138 ind./lOOO m3. Eggs abundance mean 119 /1000 m3, ranged from 9 eggs /1000 m3 to highest 590 eggs /1000 m3. Sub area East of Aru Island we found 24 families, in which dominant were Balistidae, Engraulidae, and Scaridae. Abundance of larvae mean 1126 ind/1000 m3, varied from 15 ind/1000 m3 to 3,844 ind/1000 m3. Mean abundance of eggs was 188 eggs/1000 m3, varied from 9 eg'gs/1000 m3 to 532 eggs/1000 m3. Sub area West Mapi and Mimika was found 24 families, in which the dominant are Engraulidae, Scaridae, and Clupeidae. Mean of larvae abundance 12.008 ind./lOOO m3, ranged from 13 ind./lOOO m3 to 39,356 ind./ 1000 m3. Mean abundance of eggs was 105 eggs/1000 m3, ranged from 0 /1000 m3 to 731 eggs /1000 m3. Sub area Tanjung Dolak was found 21 families, in which the dominant were Scianidae, Kyphosidae, and Clupeidae 16.35 %. Mean abundance of larva 1025 ind./lOOO m3, was least 3 ind./lOOO m3 and highest 6072 ind./lOOO m3. Mean abundance of eggs 33 /1000 m3, which it varied from 0 /1000 m3 to 149 eggs /1000 m3.